2018
DOI: 10.21608/adjg.2018.9529
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incorporating Nanocalcium Phosphate Particles into Biodentine on Pulpal Tissue Response (In Vitro Study)

Abstract: Objectives: This study was conducted to evaluate the effect of incorporating Nanocalcium phosphate (NCP) particles into Biodentine™ on pulpal tissue response as a direct pulp capping material (entire tooth culture model). Materials and methods: -A total of forty freshly human premolar teeth extracted for orthodontic reasons were used. After cavity preparation and mechanical pulp exposure, the teeth were divided into 2 main groups (20 teeth each) according to the capping material used; where group (M1) refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Results revealed that higher dentin bridge formation were associated with higher structural regularity in the organization of the sub odontoblastic layers and this observation was in agreement with previous studies as specimens with the highest cell density showed reparatory bridges with thicker and higher structural regularity (22,23) .…”
Section: Discussionsupporting
confidence: 91%
“…Results revealed that higher dentin bridge formation were associated with higher structural regularity in the organization of the sub odontoblastic layers and this observation was in agreement with previous studies as specimens with the highest cell density showed reparatory bridges with thicker and higher structural regularity (22,23) .…”
Section: Discussionsupporting
confidence: 91%
“…That was in the same line with a study showing that Ca and Si released from bioactive glass materials has the ability to stimulate proliferation of osteoblasts and expression of genes and also revealed that human dental pulp cells (HDPCs) in the bioactive glass groups proliferated throughout the culture period confirming that the ions released from bioactive glass at different time intervals did not have an inhibitory effect on cells as assessed by Alamar blue (34) . Moreover, by comparing calcium hydroxide and bioactive glass material as direct pulp capping material, it was found that higher levels of inflammation were observed in calcium hydroxide treated samples, internal resorption and abscess formation, but no internal resorption and abscess formation were observed in bioactive glass applied samples (2) .…”
Section: Discussionmentioning
confidence: 99%
“…In the 18 th century, Philip Pfaff performed the first pulp capping ever, using a small piece of gold for the healing of exposed vital pulp. According to the literature from past to present, different pulp capping materials have been used, one of them is Ca (OH) 2 (2) . Ca (OH) 2 was used as pulp capping material in conservative dentistry, when comes in direct contact with vital pulp tissues causes a small area of necrosis followed by a mild inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of 5% glass fiber powder into Biodentine was shown to significantly enhance the fracture resistance of obturated roots with the modified material when Biodentine was used as an intra-orifice barrier [16]. Aidaros and Niazy [17] assessed the pulp response to direct pulp capping with Biodentine incorporated with calcium phosphate nanoparticles (NPs). It was shown that the thickness of the dentine bridge formed by the new mixture was significantly greater than the one created by the unmodified Biodentine [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aidaros and Niazy [17] assessed the pulp response to direct pulp capping with Biodentine incorporated with calcium phosphate nanoparticles (NPs). It was shown that the thickness of the dentine bridge formed by the new mixture was significantly greater than the one created by the unmodified Biodentine [17]. Silver NPs have also been tested with Rosmarinus officinalis L. extract (ROE) and Cefuroxime.…”
Section: Introductionmentioning
confidence: 99%